The key roles of teammates, coaches, and instrumental support in adolescent sports participation: a one-year prospective study - Spruijtenburg, Gwennyth E.; van Abswoude, Femke; Platvoet, Sebastiaan W. J.; de Niet, Mark; Steenbergen, Bert (Frontiers in Sports and Active Living, 2025)
IntroductionSports participation is important for promoting lifelong health and well-being. However, it often declines during adolescence, highlighting the need to understand the factors related to adolescent sports participation. This prospective study examines the associations between different sources (e.g., family, peers, coaches, teachers) and types (e.g., emotional, instrumental, co-participation) of social support and hours of organized sports participation among secondary school students (N = 294). It also explores whether these associations change from the second to the third year of secondary education.MethodsData were collected using questionnaires and anthropometric measurements in October/November 2021 and October/November 2022. Multilevel linear fixed effects regression models were used to analyze relationships between sources and types of social support and sports participation. Additionally, scatterplots illustrated individual variability in these associations.ResultsResults showed significant associations for various sources and types of social support with organized sports participation. Social support from teammates and coaches and instrumental support emerged as the strongest predictors of hours of participation. Additionally, we found that the relationships remained stable over time. Yet, substantial individual variability in how social support related to sports participation was also observed.DiscussionThese findings emphasize the importance to promote social support from within the sports environment and to encourage instrumental support. Tailored approaches addressing individual differences are recommended to enhance adolescent sports participation.